2022
DOI: 10.3390/nu14071472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Oral Nutritional Supplements on Improving Postoperative Early Enteral Feeding Intolerance and Short-Term Prognosis for Gastric Cancer: A Prospective, Single-Center, Single-Blind, Randomized Controlled Trial

Abstract: Background: Early enteral nutrition (EN) after abdominal surgery can improve the prognosis of patients. However, the high feeding intolerance (FI) rate is the primary factor impeding postoperative EN. Methods: Sixty-seven patients who underwent radical subtotal or total gastrectomy for gastric cancer (GC) were randomly allocated to the preoperative oral nutritional supplement group (ONS group) or dietary advice alone (DA group). Both groups were fed via nasojejunal tubes (NJs) from the first day after surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…With such limited exposure, these interventions are less likely to demonstrate benefits on early postoperative outcomes. Our findings support that at least two weeks of surgical prehabilitation are necessary to expect an impact [ 28 , 29 , 30 , 32 , 38 ]. Unfortunately, in GI cancer resections, time is often considered of the essence to avoid disease progression, although this concept is challenged [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…With such limited exposure, these interventions are less likely to demonstrate benefits on early postoperative outcomes. Our findings support that at least two weeks of surgical prehabilitation are necessary to expect an impact [ 28 , 29 , 30 , 32 , 38 ]. Unfortunately, in GI cancer resections, time is often considered of the essence to avoid disease progression, although this concept is challenged [ 59 , 60 ].…”
Section: Discussionsupporting
confidence: 83%
“…He et al compared a 1-week EN intervention to dietary advice alone in patients with malignant gastric cancer [ 28 ]. Most patients were malnourished.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical trials have found that nutritional interventions during 90 days of hospitalization and after discharge can improve the nutritional status, grip strength and in ammatory prognostic indicators of malnourished patients, but have little bene t in reducing readmission rates and improving weight loss [12][13] . However, other clinical trials found that nutritional interventions during 30 days in hospital and after discharge could not signi cantly improve the perioperative serum index, short-term prognosis or postoperative complication rate of malnourished patients [14][15] . Long-term nutrition interventions seem to be more effective than short-term interventions.…”
Section: Introductionmentioning
confidence: 96%
“…Early enteral nutrition (EN) can reduce the inflammatory response, nourish the intestinal mucosa, prevent bacterial translocation, and reduce postoperative infectious complications (He et al, 2022).…”
Section: Introductionmentioning
confidence: 99%